Special Educational Needs and parental involvement - Felizardo, Sara (2017)
Parental involvement is a multifaceted concept that encompasses different contexts and can be presented in various formats. Within the inclusive approach, the collaborative model and partnership of parental involvement provides a frame of reference that can help support professionals, educators and teachers in their contacts with parents of children with SEN. It seems to be consensual in the scientific literature it´s benefits in child and family development, as well as the work of the teacher and the school context (Englund, Luckner, Whaley & Egeland, 2004; Epstein, 1987, 1992; Grolnick & Slowiaczeck, 1994; Swick, 2007; Kohl, Lengua & McMahon, 2000). In the framework of inclusive approach, the collaborative model of parental involvement (Fine & Nissenbaum, 2000) based on a set of core ideas which, in summary, highlight the following aspects: include the parents in decisions related to the child; educate parents to participate in decisions that have to do with the child; focus on the more positive and constructive aspects of family events; support the parents to enable them for a greater participation; promote the empowerment of parents to work actively in the development and wellbeing of children. Parental and family involvement in the education of children and youth with disabilities has become one of the main purposes of professionals working in this area. The benefits in terms of planning and implementation of interventions have been widely documented by several studies (Dunst, Trivette & Deal, 1994; Simeonsson & Bailey, 1990; Turnbull & Turnbull, 1990). METHODOLOGY - This is an descriptive-correlational research with a non-probability convenience sample of 256 pare of children with and without SEN, and 107 teachers of regular and special education. The study was undertaken in schools and institutions of support for disabled children of the Municipality of Viseu, and data were collected with a questionnaire about parental involvement in school. The instruments for data collection were: i) "Parental Involvement in School Questionnaires" (PISQ), parents version (PaV) and teachers version (TeV) produced by Pereira, Canavarro, Mendonca and Cardoso (2003), with the theoretical model Epstein (1987, 1992); ii) Parental Questionnaire (sociodemographic, family and school data). GOALS - This study aims to analyze the relationships between the parent`s perspectives of children with Special Educational Needs/ SEN and teachers of regular and special education, about parental involvement in school. RESULTS & DISCUSSION - The comparative analysis of perceptions of the total sample of parents (n=256) with those of regular education teachers suggests that although the mean values parent be higher M=69,56 (SD=12,07), there are no differences with statistical significance (t= 1,582; p= 0,115). These results do not converge with those of Pereira et al. (2003), who found significant differences. We performed a similar procedure for subgroups of parents and found that there were differences with statistical significance (t=3,748; p=0,000) between parents of children with disabilities (n=107) and regular education teachers parents’ average is higher M=63,88; (SD=13,28) than teachers’ M=59,70 SD=14,09), but the same does not occur (t=-0,966; p= 0,336) in the case of parents of children without disabilities (n=149). We further note that there are no significant differences between special education teachers and parents of children with disabilities parents M=63,88 (SD=13,28); teachers M=64,04 (SD=15,60). With regard to the differences in perceptions of engagement between the two groups of teachers, found that the average of special education teachers is statistically superior (t= 4,565; p= 0,000). Data suggests differences between perceptions of regular education teachers and parents of children with SEN, likewise the perceptions between the two type of teachers, which indicate that the work should evolve towards greater convergence and articulation, in order to delineate forms of intervention converging and promote a greater parental involvement as part of a collaborative and partnership approach.